2011
DOI: 10.1002/jbmr.437
|View full text |Cite
|
Sign up to set email alerts
|

Association of the α2δ1 subunit with Cav3.2 enhances membrane expression and regulates mechanically induced ATP release in MLO-Y4 osteocytes

Abstract: Voltage sensitive calcium channels (VSCCs) mediate signaling events in bone cells in response to mechanical loading. Osteoblasts predominantly express L-type VSCCs composed of the α1 pore-forming subunit and several auxiliary subunits. Osteocytes, in contrast, express T-type VSCCs, but a relatively small amount of L-type α1 subunits. Auxiliary VSCC subunits have several functions including modulating gating kinetics, trafficking of the channel and phosphorylation events. The influence of the α2δ auxiliary subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 54 publications
4
71
0
1
Order By: Relevance
“…T-type Ca 2+ channels are highly expressed in many developing tissues and are implicated in regulating cellular events leading to cell proliferation and differentiation (50). Calcium influx through T-type Ca 2+ channels activates several cellular pathways, including calcineurin/NFAT (29,39), extracellular signal-regulated kinase (31,(51)(52)(53), nitric oxide synthase 3 (54), and Ca 2+ /calmodulindependent protein kinase II (55). However, the detailed mechanisms linking these T-type Ca 2+ channel-activated signaling pathways to cell proliferation and differentiation are not completely clear.…”
Section: Discussionsupporting
confidence: 43%
“…T-type Ca 2+ channels are highly expressed in many developing tissues and are implicated in regulating cellular events leading to cell proliferation and differentiation (50). Calcium influx through T-type Ca 2+ channels activates several cellular pathways, including calcineurin/NFAT (29,39), extracellular signal-regulated kinase (31,(51)(52)(53), nitric oxide synthase 3 (54), and Ca 2+ /calmodulindependent protein kinase II (55). However, the detailed mechanisms linking these T-type Ca 2+ channel-activated signaling pathways to cell proliferation and differentiation are not completely clear.…”
Section: Discussionsupporting
confidence: 43%
“…Reports of force-induced mobilization and action of such molecules as PGE 2 (41,42), NO (25,43), VEGF (20), RANKL, OPG (44), ATP (30,45), and Ca 2+ (18,22) affirm autocrine/paracrine signaling in MLO-Y4 cells. Our evaluation of P2R signaling dynamics in MLO-Y4 cells after incubation with the broad-spectrum P2 receptor antagonist suramin demonstrated suppressed effector responses of MLO-Y4 cells, consistent with previously reported suramin-induced interference with P2Y and P2X receptor binding sites that blocked the action of ATP on purinergic receptors and subsequent signaling cascades (46,47).…”
Section: Discussionmentioning
confidence: 42%
“…7,15,19 Lots of studies indicated that ATP could release from the mechanically stimulated osteoblasts or osteocytes and further binds the purinergic P2 receptor on the neighboring cells to cause the calcium release from ER. 10,40 It has been found that the P2X7 receptor is expressed in osteoclasts, 21 which may contribute to cell-cell calcium transfer. The influence of P2 receptors on osteoclast physiology and bone physiology in general is beginning to be understood.…”
Section: Introductionmentioning
confidence: 40%